Adolescent athletes' sleep problems and overtraining <subtitle>A case study</subtitle> - Unjung Cho; KyoungBin Im (Hogrefe AG, 2024)
Abstract: Introduction: Sleep is crucial for athletes' recovery and performance while overtraining can negatively affect sleep quantity and sleep quality. We present a case of a 16-year-old female athlete exploring the reciprocal negative effects of overtraining and sleep problems on each other. Methods: A flyer of a high school cheerleading team with a history of injuries, irregular menses, chronic fatigue, and various sleep-related complaints presented with declining athletic performance. Results: After medical causes were ruled out, sleep disorders such as insomnia, restless legs syndrome and delayed sleep phase were identified and treated. Despite treatment, her daytime sleepiness and sleep attacks persisted and thus necessitated further investigation. Comprehensive sleep studies, including actigraphy, polysomnography, and multiple sleep latency testing, ultimately revealed insufficient sleep syndrome as the underlying cause. Notably, periods of reduced training intensity coincided with significant improvements in her daytime sleepiness. Conclusion: This case highlights the importance of comprehensive sleep-wake assessments for adolescent athletes to accurately diagnose sleep disorders in the context of overtraining. Prioritizing sleep is crucial for optimizing athletic performance in young athletes by preventing and managing overtraining-related sleep disorders.